Drug-Loaded, Polyurethane Coated Nitinol Stents for the Controlled Release of Docetaxel for the Treatment of Oesophageal Cancer - Paris Fouladian; Qiuyang Jin; Mohammad Arafat; Yunmei Song; Xiuli Guo; Anton Blencowe; Sanjay Garg (MDPI AG, 2021)
For several decades, self-expanding metal stents (SEMSs) have shown significant clinical success in the palliation of obstructive metastatic oesophageal cancer. However, these conventional oesophageal stents can suffer from stent blockage caused by malignant tumour cell growth. To overcome this challenge, there is growing interest in drug-releasing stents that, in addition to palliation, provide a sustained and localized release of anticancer drugs to minimise tumour growth. Therefore, in this study we prepared and evaluated an oesophageal stent-based drug delivery platform to provide the sustained release of docetaxel (DTX) for the treatment of oesophageal cancer-related obstructions. The DTX-loaded oesophageal stents were fabricated via dip-coating of bare nitinol stents with DTX-polyurethane (PU) solutions to provide PU coated stents with DTX loadings of 1.92 and 2.79% w/w. Mechanical testing of the DTX-PU coated stents revealed that an increase in the drug loading resulted in a reduction in the ultimate tensile strength, toughness and Young's modulus. In vitro release studies showed a sustained release of DTX, with ~80-90% released over a period of 33 days. While the DTX-loaded stents exhibited good stability to gamma radiation sterilisation, UV sterilisation or accelerated storage at elevated temperatures (40 °C) resulted in significant DTX degradation. Cell proliferation, apoptosis and Western blotting assays revealed that the DTX released from the stents had comparable anticancer activity to pure DTX against oesophageal cancer cells (KYSE-30). This research demonstrates that the dip-coating technique can be considered as a promising approach for the fabrication of drug-eluting stents (DESs) for oesophageal cancer treatment.